Gastrointestinal Biopsies for the Diagnosis of Alpha-Synuclein Pathology in Parkinson’s Disease - Maria Graciela Cersosimo (Gastroenterology Research and Practice)
The diagnosis of Parkinson’s disease (PD) relies on clinical features whereas pathological confirmation is only possible with autopsy examination. The neuropathological hallmarks of PD are neuronal loss and the presence of inclusions termed Lewy bodies/neurites in affected regions. A major component of these inclusions is phosphorylated alpha-synuclein (α-SYN) protein. There is evidence that α-SYN pathology is widely distributed outside the central nervous system in patients with PD. The gastrointestinal tract is importantly affected by α-SYN containing inclusions and typically there is a rostrocaudal gradient for the distribution of the pathology. The highest amounts of Lewy bodies/neurites are found at the submandibular gland together with the lower esophagus and the lowest amounts are found in the rectum. Autopsy findings prompted research aimed at achieving in vivo pathological diagnosis of PD by demonstrating the presence of α-SYN pathology in biopsy material of these peripheral accessible tissues. So far, biopsy studies of the gut have demonstrated the presence of α-SYN pathology in the salivary glands, stomach, duodenum, colon, and rectum. Further research is necessary in order to determine which are the most sensitive targets for in vivo α-SYN pathology detection and the safest techniques for these approaches in patients with PD.